Efektivitas Mekanisme Putusan Pelaksanaan Dan Pembatalan Putusan Arbitrase Dalam Sistem Hukum Indonesia - Putri Kurnia Sari; Izwan Hafizi (4, 2026)
This research examines three fundamental aspects of Indonesian arbitration law arbitral awards, the enforcement of arbitral awards, and the annulment of arbitral awards based on Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution, as well as the latest regulatory development, Supreme Court Regulation (PERMA) Number 3 of 2023. The research employs a normative legal method using the statute approach, conceptual approach, and case approach, through an examination of two important decisions: the dispute between Pertamina and Karaha Bodas Company, and the dispute between Astro Nusantara and PT Ayunda Prima Mitra. The findings show that arbitral awards are final and binding, yet their enforcement both domestic and international still faces technical, procedural, and jurisdictional obstacles. The annulment of arbitral awards is only permitted on the limited grounds set out in Article 70 of Law No. 30 of 1999, although in judicial practice the scope of these grounds is often interpreted extensively. The issuance of PERMA No. 3 of 2023 provides new procedural certainty, particularly regarding the timeframe for granting exequatur, but has not yet fully resolved the problem of annulment petitions being misused as a tactic to delay execution. This research recommends amending Law No. 30 of 1999, strengthening the capacity of district court judges, and establishing sanctions against annulment petitions filed in bad faith, in order to enhance the effectiveness of arbitration as a means of resolving business disputes in Indonesia. If you'd like, I can also help refine this into a more formal academic-abstract register (e.g., adjusting terminology like